2019
DOI: 10.1177/1753466619860058
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbidities on mortality among men and women with COPD: report from the OLIN COPD study

Abstract: Background: Comorbidities probably contribute to the increased mortality observed among subjects with chronic obstructive pulmonary disease (COPD), but sex differences in the prognostic impact of comorbidities have rarely been evaluated in population-based studies. The aim of this study was to evaluate the impact of common comorbidities, cardiovascular disease (CVD), diabetes mellitus (DM), and anxiety/depression (A/D), on mortality among men and women with and without airway obstruction in a population-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
(53 reference statements)
3
18
0
1
Order By: Relevance
“…Depression frequently co-exists in patients with respiratory disorders such as asthma and COPD 22 , 23 ; in our study, it was common comorbidity in clusters with cardiometabolic diseases. In women, depression was amongst the main conditions in two multimorbidity clusters, the dyslipidemic-depressive, and the depressive-degenerative clusters.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Depression frequently co-exists in patients with respiratory disorders such as asthma and COPD 22 , 23 ; in our study, it was common comorbidity in clusters with cardiometabolic diseases. In women, depression was amongst the main conditions in two multimorbidity clusters, the dyslipidemic-depressive, and the depressive-degenerative clusters.…”
Section: Discussionsupporting
confidence: 46%
“…In the last one, we found that depression was associated with hypertension, congestive heart failure, and degenerative diseases, with significantly high mortality risk. A recent study in COPD patients reported that cardiovascular disease is more prevalent in men, but its impact on mortality is higher in women, and that although depression is more common in women, its impact on mortality is similar in both genders 23 .…”
Section: Discussionmentioning
confidence: 97%
“…In the study of Sawalha et al, the most common comorbidities in men were cardiovascular disease and diabetes mellitus, while in women anxiety and depression. Hypertension is a disorder of lipid metabolism and obesity 35 . This finding also confirms the results of the García et al, showing that common comorbidities in 3183 people with COPD in Spain included diabetes, high blood pressure, lipid metabolism disorders, and obesity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of co-morbidity also varied with gender in COPD patients and men were described to be more susceptible to CV and diabetes mellitus (10).…”
Section: Introductionmentioning
confidence: 99%